Basic Tendencies of Work of Pedagogical Practice Department at Khmelnitsky Humanitarian-Pedagogical Academy - Natalya Kazakova (Pedagogical Discourse, 2012)
On the basis of work experience main directions of work of pedagogical practice department at Khmelnitsky Humanitarian-Pedagogical Academy have been defined in the article. To them belong: organizational, methodical, scientific work with the students, with supervisors of practice at the Academy and bases of practice; analysis of practice’s results; control and management of practice and also their content is revealed.